24. Season five [videorecording (DVD)] - Sutherland, Kiefer, 1966-; Bernard, Carlos; Raver, Kim, 1969- (20th Century Fox Home Entertainment, 2006)
Eighteen months after faking his own death, Jack Bauer is forced to return to Los Angeles when it becomes apparent that the only four people who know he is still alive are being systemically targeted for assassination. The assassinations coincide with the signing of an anti-terrorism treaty between Russia and the U.S., leading Jack to suspect a link between the assassinations, the treaty, and a group of Russian terrorists.